A comparison between ginger and metoclopramide in the prevention of post operative nausea and vomiting in hospital universiti sains malaysia - Nagarajan , Nagalingam (2011)
Background: In general in today’s modern world, post operative nausea and vomiting is as common as 30 % of the total patients going under anaesthesia through multiple studies (Lermen J. et al. 1992, Saeeda I. et al. 2004) done around the globe. Post operative nausea and vomiting is a very disturbing outcome after anaesthesia. It may be managed with modern medicine, such as metoclopramide or with alternative medication, such as ginger as studied in this dissertation. Methodology: This is a randomized controlled trial study to look at effectiveness of ginger against a commonly used, metoclopramide as an anti emetic agent to prevent post operative nausea and vomiting. Patients were grouped into 2 comparable arms in a double blinded method to look at outcome symptoms of nausea, retching and vomiting. Primary and secondary statistical analysis were used to look at the association of post operative nausea, retching and vomiting against tablet metoclopramide and ginger given prior to anaesthesia. Results: The demographic characteristics were comparable between both groups. There was a significant finding statistically with p-value of 0.025 through Fisher’ exact test for association between post operative vomiting within 6 hours for ginger group against metoclopramide group. Other findings of the outcome symptoms of nausea and retching within 0 to 6 hours and more than 6 hours to 12 hours as well as vomiting more than 6 hours to 12 hours were not statistically significant. Conclusion: This significant results of effectiveness of ginger as a preventive for post operative vomiting is a very promising finding in anaesthetic medical practices. We believe the positive result of ginger will be a catalyser for future study on the effectiveness of ginger in Malaysia. Ultimately, this will help in development of our holistic medicine in Malaysia.